Digital Human Resource Management in Border Public Organizations: A Systematic Literature Review - Angga Tritisari; Maria Cristiana Iman Kalis; M.Irfani Hendri (International Journal of Multidisciplinary Sciences and Arts, 2026)
Digital transformation in the public sector drives the adoption of Digital Human Resource Management (Digital HRM) as a strategic tool to improve organizational efficiency and public service quality. However, existing studies remain scattered and fail to fully capture the interrelationships between driving factors, barriers, and organizational outcomes, particularly in border regions facing infrastructure and resource constraints. This study conducts a systematic literature review (SLR) to examine Digital HRM's role in influencing public sector organizational outcomes and to identify its implementation drivers and barriers. From a total of 320 articles identified in the initial stage, a screening process was conducted, reducing the list to 60 articles; ultimately, 30 empirical studies meeting the inclusion criteria were analyzed in greater depth. Study quality was evaluated using the Mixed Methods Appraisal Tool (MMAT), and data synthesis was conducted via deep thematic analysis.Findings indicate that Digital HRM adoption is shaped by technological, organizational, human, and institutional factors, with perceived usefulness, organizational readiness, and leadership support being the most significant drivers. Conversely, resistance to change, infrastructure limitations, and digital skills gaps serve as major barriers. Implementation successfully enhances operational efficiency, service quality, employee performance, and decision-making quality, often mediated by employee engagement and knowledge sharing. In border regions, limited connectivity and resources are critical factors determining implementation effectiveness. This study contributes a comprehensive synthesis of Digital HRM dynamics in the public sector and broadens theoretical perspectives by integrating the border region context, offering a solid foundation for formulating tailored future policies.